VS-5584 Inhibits Human Osteosarcoma Cells Growth by Induction of G1-phase Arrest through Regulating PI3K/mTOR and MAPK Pathways - Sun, Jing-Yi; Hou, Ya-Jun; Cui, Hai-Juan; Zhang, Cheng; Yang, Ming-Feng; Wang, Feng-Ze; Sun, Zheng; Fan, Cun-Dong; Sun, Bao-Liang; Oh, Jin R. (Current Cancer Drug Targets, 2020)
Background: Activation of the PI3K/mTOR signaling pathway plays a key role in the progression of human osteosarcoma. Studies have confirmed that VS-5584 was a novel inhibitor of the PI3K/mTOR pathway, and displayed potential anticancer activity. Objective: To explore the anticancer effect and underlying mechanism of VS-5584 against the growth of human osteosarcoma cells. Methods: U2OS and MG-63 human osteosarcoma cells were cultured and the cytotoxicity, cell apoptosis in VS-5584-treated cells were explored by the CCK8 assay, flow cytometric analysis and western blot. Cell migration and tube formation were also employed to examine the anticancer potential. Results: The results showed that VS-5584 treatment dose-dependently inhibited the growth of U2OS and MG-63 cells by induction of G1-phase arrest through regulating p21, p27, Cyclin B1 and Cdc2. Further investigation revealed that VS-5584 treatment effectively inhibited the PI3K/mTOR signaling pathway and triggered MAPK phosphorylation. Moreover, VS-5584 treatment dramatically suppressed cell migration and tube formation of HUVECs, followed by the down-regulation of HIF-1α and VEGF. Conclusion: Our findings validated that VS-5584 may be a promising anticancer agent with potential application in the chemotherapy and chemoprevention of human osteosarcoma.
Keywords: G1-phase arrest